Tenebrio molitor (yellow mealworms) as potential ‘nutrient concentrators’ for sustainable animal feeds - Hawkey, Kerensa J. (2022)
Alternative protein sources are urgently needed to replace the traditional sources for animal feeds (e.g. soybean meal). Mealworms are being investigated as one such source, due to similar nutrient composition to soybean meal, but production methods and feed sources need to be sustainable for it to be an effective replacement feed ingredient. There is large variation in production methods and already available technologies in conventional livestock production, such as commercial enzymes have not been utilised in insect production.